PROBLEM SOLVING SKILLS REQUIRED BY PRINCIPALS IN THE MANAGEMENT OF HUMAN RESOURCES IN PUBLIC SECONDARY SCHOOLS IN ENUGU STATE (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study was conducted to determine the problem solving skills required by principals in the management of human resources in public secondary schools in Enugu State and was guided by two research questions with two corresponding null hypotheses. The study adopted a descriptive survey research design with the population of 8,463 teachers in all the 297 public secondary schools in Enugu State with a sample size of 233 respondents. This includes 103 male and 130 female teachers obtained using purposive sampling technique. The instrument used for data collection was a structured questionnaire developed by the researcher titled “Problem Solving Skills required by Principals in the Management of Human Resources Questionnaire (PSSPMHRQ)”. The instrument was validated by three research experts; two experts from the Department of Educational Management while one from theMeasurement and Evaluation Unit of Department of Mathematics and Computer Education, of Enugu State University of Science and Technology.The overall reliability index of 0.77 was obtained using Cronbach alpha. The research questions raised were answered in line with the two specific purposes of the study using mean statistics and standard deviation while the null hypotheses formulated were tested at .05 level of significance and appropriate degree of freedom using t-test in SPSS. The result of the analysis showed among others that creative thinking skill with Mean (x) of 3.12 and Standard deviation (SD) of 0.84 and critical thinking skill with (x) of 3.19 and SD of 0.87 are required by principals in the management of human resources in public secondary schools in Enugu State. The study recommends among others that secondary school principals should ensure the acquisition of saleable problem solving skills to enhance the management of human resources in public secondary schools in Enugu State, and more emphasis should be made by appropriate authorities on the need to develop creative thinking skills for effective work output in public secondary schools in Enugu.